Efektivitas Terapi Musik terhadap Kecemasan dan Nyeri Pasien Coronary Artery Bypass Graft - Sari Eprina Nadeak; Muhammad Adam; Riri Maria (Journal of Telenursing (JOTING), 2021)
This study aims to identify the effectiveness of music therapy in reducing anxiety and pain levels in patients with Coronary Artery Bypass Graft (CABG) surgery. The method used in this research is a literature review by searching online databases: Ebscohost, Wiley Online, Proquest, Pubmed, & ScienceDirect. The results showed that music therapy was effective in reducing anxiety and pain. The type of music provided is mostly natural music, the duration is 20-30 minutes and the level is 25-60 dB. In conclusion, music therapy effectively reduces anxiety and pain in patients with CABG surgery. Keywords: Anxiety, Pain, CABG Surgery, Music Therapy